Tumor Control Probability Modeling for Radiation Therapy of Keratinocyte Carcinoma - Phillip Prior; Musaddiq J. Awan; J Frank Wilson; X. Allen Li (Frontiers in Oncology, 2021)
SummarySkin cancer patients may be treated definitively using radiation therapy (RT) with electrons, kilovoltage, or megavoltage photons depending on tumor stage and invasiveness. This study modeled tumor control probability (TCP) based on the pooled clinical outcome data of RT for primary basal and cutaneous squamous cell carcinomas (BCC and cSCC, respectively). Four TCP models were developed and found to be potentially useful in developing optimal treatment schemes based on recommended ASTRO 2020 Skin Consensus Guidelines for primary, keratinocyte carcinomas (i.e. BCC and cSCC).BackgroundRadiotherapy (RT) with electrons or photon beams is an excellent primary treatment option for keratinocyte carcinoma (KC), particularly for non-surgical candidates. Our objective is to model tumor control probability (TCP) based on the pooled clinical data of primary basal and cutaneous squamous cell carcinomas (BCC and cSCC, respectively) in order to optimize treatment schemes.MethodsPublished reports citing crude estimates of tumor control for primary KCs of the head by tumor size (diameter: ≤2 cm and >2 cm) were considered in our study. A TCP model based on a sigmoidal function of biological effective dose (BED) was proposed. Three-parameter TCP models were generated for BCCs ≤2 cm, BCCs >2cm, cSCCs ≤2 cm, and cSCCs >2 cm. Equivalent fractionation schemes were estimated based on the TCP model and appropriate parameters.ResultsTCP model parameters for both BCC and cSCC for tumor sizes ≤2 cm and >2cm were obtained. For BCC, the model parameters were found to be TD50 = 56.62 ± 6.18 × 10-3 Gy, k = 0.14 ± 2.31 × 10−2 Gy−1 and L = 0.97 ± 4.99 × 10−3 and TD50 = 55.78 ± 0.19 Gy, k = 1.53 ± 0.20 Gy−1 and L = 0.94 ± 3.72 × 10−3 for tumor sizes of ≤2 cm and >2 cm, respectively. For SCC the model parameters were found to be TD50 = 56.81 ± 19.40 × 104 Gy, k = 0.13 ± 7.92 × 104 Gy−1 and L = 0.96 ± 1.31 × 10-2 and TD50 = 58.44 ± 0.30 Gy, k = 2.30 ± 0.43 Gy−1 and L = 0.91± 1.22 × 10−2 for tumors ≤2cm and >2 cm, respectively. The TCP model with the derived parameters predicts that radiation regimens with higher doses, such as increasing the number of fractions and/or dose per fraction, lead to higher TCP, especially for KCs >2 cm in size.ConclusionFour TCP models for primary KCs were developed based on pooled clinical data that may be used to further test the recommended kV and MV x-ray and electron RT regimens from the 2020 ASTRO guidelines. Increasing both number of fractions and dose per fraction may have clinically significant effects on tumor control for tumors >2 cm in size for both BCC and cSCC.